Parallel generation of meshes with cracks using binary spatial decomposition. (October 2016) - Freitas, Markos; Wawrzynek, Paul; Cavalcante-Neto, Joaquim; Vidal, Creto; Carter, Bruce; Martha, Luiz; Ingraffea, Anthony
Abstract This work describes a technique to generate tetrahedral meshes with cracks using parallel computers with distributed memory. This technique can be used for models without cracks as well. It employs a binary partitioning structure that uses axis-aligned planes to decompose the domain. Those decomposing planes are determined based on a refined octree that is built to estimate the amount of work necessary to generate the whole mesh, so that the amount of work in each subdomain is approximately the same. A serial advancing front technique is used in each subdomain concurrently, in such a way that the generated tetrahedra do not cross the decomposing planes. After local synchronizations, meshes are generated interfacing the subdomains. The results show that the prediction of the number of elements in each subdomain is accurate, leading to a well-balanced algorithm and to a good speed-up. Also, the meshes generated in parallel have very good quality, similar to the that of a serially generated mesh.